The Effects of Schooling on Wealth Accumulation Approaching Retirement - Paul Bingley; Alessandro Martinello (Lund University, School of Economics and Management, Department of Economics, 2017)
Education and wealth are positively correlated for individuals approaching retirement, but the direction of the causal relationship is ambiguous in theory and has not been identified in practice. We combine administrative data on individual total wealth with a reform expanding access to lower secondary school in Denmark in the 1950s, finding that schooling increases pension annuity claims but reduces the non-pension wealth of men in their 50's. These effects grow stronger as normal retirement age approaches. Labour market mechanisms are key, with schooling increasing job mobility, reducing housing equity, increasing leverage, and improving occupational pension benefits.
Keywords: D31; G11; I24; I26; 330; Education; Wealth; Labour market mechanisms; Pensions; Housing equity; Portfolio composition; Instrumental variable